Adsorption behaviour of Si-MCM-41 for CO2: Effect of pressure and temperature on adsorption - Ramli, A. (Italian Association of Chemical Engineering - AIDIC, 2014)
Adsorption process is an alternative process for CO2 removal which could offer solutions to the existing problems associated with absorption process. A suitable adsorbent which has high adsorption capacity and selectivity for CO2 is required in adsorption process. Highly ordered siliceous mesoporous molecular sieve, Si-MCM-41 which has high surface area and large pore volume is an attractive candidate for use as adsorbent in the adsorption separation. Si-MCM-41 material was synthesized by hydrothermal process at 100 oC for 8 days then dried at 120 oC for 24 hours and finally calcined at 550 oC for 6 hours. Calcined Si-MCM-41 was characterized by XRD, FTIR, HRTEM and N2 physisorption. All the characterization results confirm that the synthesized material is Si-MCM-41. Adsorption behaviour of Si-MCM-41 for CO2 was investigated at temperatures between 25 - 100 oC and pressures from 0 - 20 bar using Rubotherm gravimetric-densimetric apparatus. Si-MCM-41 showed low adsorption capacity of 27.43 mg-CO2/g-adsorbent at 1 bar and 25 oC. This low adsorption of CO2 on Si-MCM-41 could be attributed to the weak interaction between the siliceous material and CO2. Results show that adsorption of CO2 increases with increasing pressure and at it reaches to 296.48 mg CO2/g-adsorbent at 20 bar which can be explained as the CO2 molecules are forced into the deep inside the pores of Si-MCM-41 at high pressure. The Si-MCM-41 material also shows an increased in CO2 adsorption with increased temperature with 335.77 mg-CO2/g-adsorbent adsorbed at 50 oC. However, further increase in temperature to 75 oC and 100 oC decreases the adsorption of CO2 to 295.07 mg-CO2/g-adsorbent and 269.86 mg-CO2/g-adsorbent, respectively. This decrease in adsorption is suggested due to weakening of the Van der Waals forces between Si-MCM-41 and CO2. Overall results show that Si-MCM-41 has high potential to be used as adsorbent for CO2 removal at pressures up to 20 bar and temperatures up to 75 oC. Copyright Â© 2014 AIDIC Servizi S.r.l.